Virtual collaboration : work from anywhere, overcommunicate, avoid isolation - Thomas, James Edward (20 minute manager series., 2023)
Working remotely gives you flexibility and independence. But it can pose challenges when you need to team up with colleagues or coworkers. Virtual Collaboration covers the basics of working productively-and collaboratively-from anywhere. You'll learn to: - Communicate clearly over a variety of media - Bond with colleagues across the wires - Keep others-and yourself-accountable - Avoid and mitigate tech glitches Don't have much time? Get up to speed fast on the most essential business skills with HBR's 20-Minute Manager series. Whether you need a crash course or a brief refresher, each book in the series is a concise, practical primer that will help you brush up on a key management topic. Advice you can quickly listen to and apply, for ambitious professionals and aspiring executives-from the most trusted source in business.